CICLO DE VIDA Y FORMAS JUVENILES DE EURYMETOPUM MULTINOTATUM PIC, 1950 (COLEOPTERA: CLERIDAE: PHYLLOBAENINAE) - Solervicens, Jaime; Huarapil, Silvia (Acta Entomológica Chilena, 2022)
The life cycle of Eurymetopum multinotatum Pie, 1950 (Coleóptera, Cleridae), under laboratory conditions, is studied in this paper. The stock examples were collected from the Reserva Nacional Río Clarillo, Región Metropolitana de Santiago, trying to secure fertilized females. The ovipositional characteristics of the species, the duration and permanence of the different stages, i.e., immatures and adults, and natural mortality and survival of them, are recognized. All these stages are described and illustrated.